PENERAPAN SISTEM MANAJEMEN MUTU PELAKSANAAN PEKERJAAN LAPIS PONDASI AGREGAT PADA JALAN PROVINSI DI PROVINSI JAWA TENGAH - Muballigh .; Agus Taufik Mulyono (Jurnal Transportasi, 2018)
Abstract Road pavement is often damaged before the design life caused by the quality of the base layer material and the foundation layer density is not achieved. Work Instruction which refers to the general specifications of the Directorate General of Highways, which is prepared as a guide in monitoring the implementation of road construction work, is very necessary so that the construction work of provincial road aggregate base can be carried out according to the correct working method. The purpose of this study was to determine the implementation of the quality management system of aggregate base work and the achievement of the quality performance of its implementation. The data were analyzed on the level of importance of the implementation of aggregate base work based on the respondents' answers, which consisted of parties directly involved in the implementation of provincial road construction work in Central Java Province. Analysis is performed using Structural Equation Modeling. The results obtained show that the contribution of weighting influence to the subcomponents of preparation, implementation, compaction, and compaction improvement was 70.5%, 50.6%, 76.0%, and 94.7% respectively. The assessment of the achievement of the quality performance of the implementation of aggregate base work is 82.49% and is included in the medium category. Keywords: base layer, quality management system, road construction, provincial roads  Abstrak Perkerasan jalan sering mengalami kerusakan sebelum umur rencana yang disebabkan oleh mutu material lapis pondasi rendah dan kepadatan lapis pondasi tidak tercapai. Instruksi Kerja yang mengacu pada spesifikasi umum Direktorat Jenderal Bina Marga, yang disusun sebagai panduan dalam pengawasan pelaksanaan pekerjaan konstruksi jalan, sangat diperlukan agar pekerjaan konstruksi lapis pondasi agregat jalan provinsi dapat dilaksanakan sesuai metode kerja yang benar. Tujuan penelitian ini adalah untuk mengetahui pelaksanaan sistem manajemen mutu pekerjaan lapis pondasi agregat dan capaian kinerja mutu pelaksanaannya. Data dianalisis terhadap tingkat kepentingan pelaksanaan pekerjaan lapis pondasi agregat berdasarkan jawaban responden, yang terdiri atas pihak-pihak yang terlibat langsung dalam pelaksanaan pekerjaan konstruksi jalan provinsi di Provinsi Jawa Tengah. Analisis dilakukan dengan menggunakan Structural Equation Modeling. Hasil yang diperoleh menunjukkan bahwa kontribusi bobot pengaruh untuk subkomponen persiapan, pelaksanaan, pemadatan, dan perbaikan pemadatan adalah 70,5%, 50,6%, 76,0%, dan 94,7% berturut-turut. Penilaian capaian kinerja mutu pelaksanaan pekerjaan lapis pondasi agregat adalah sebesar 82,49% dan termasuk dalam kategori medium. Kata-kata kunci: lapis pondasi, sistem manajemen mutu, konstruksi jalan, jalan provinsi